2022
DOI: 10.1002/jbio.202100274
|View full text |Cite
|
Sign up to set email alerts
|

Discriminating cell line specific features of antibiotic‐resistant strains of Escherichia coli from Raman spectra via machine learning analysis

Abstract: While Raman spectroscopy can provide label‐free discrimination between highly similar biological species, the discrimination is often marginal, and optimal use of spectral information is imperative. Here, we compare two machine learning models, an artificial neural network and a support vector machine, for discriminating between Raman spectra of 11 bacterial mutants of Escherichia coli MDS42. While we find that both models discriminate the 11 bacterial strains with similarly high accuracy, sensitivity and spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…[ 176 ] Zahn et al. [ 177 ] used ANN and SVM models to distinguish the Raman spectra of 11 E. coli strains, respectively. They experimentally demonstrated that both methods could potentially analyze complex spectral datasets for biomedical applications, with SVM showing better results on small datasets and ANN with relatively complex structures showing better results on large datasets.…”
Section: Application Of ML and Raman Spectroscopy In Biomedicinementioning
confidence: 99%
See 2 more Smart Citations
“…[ 176 ] Zahn et al. [ 177 ] used ANN and SVM models to distinguish the Raman spectra of 11 E. coli strains, respectively. They experimentally demonstrated that both methods could potentially analyze complex spectral datasets for biomedical applications, with SVM showing better results on small datasets and ANN with relatively complex structures showing better results on large datasets.…”
Section: Application Of ML and Raman Spectroscopy In Biomedicinementioning
confidence: 99%
“…KPCA extracts the nonlinear features of the raw data and evaluates and discriminates individual bacterial cells at the serotype level by a DT algorithm with classification accuracy in the range of 87.1%-95.8%. [176] Zahn et al [177] used ANN and SVM models to distinguish the Raman spectra of 11 E. coli strains, respectively. They experimentally demonstrated that both methods could potentially analyze complex spectral datasets for biomedical applications, with SVM showing better results on small datasets and ANN with relatively complex structures showing better results on large datasets.…”
Section: Ml-assisted Raman Spectroscopy Of Pathogenmentioning
confidence: 99%
See 1 more Smart Citation
“…CNN is suitable for multi‐classification analysis for in‐depth mining and interpretation of Raman spectra. A study compared two machine learning models (an artificial neural network and a SVM) for the discrimination between 11 bacterial mutants of E. coli with Raman spectroscopy 73 . Both models were found to have similarly high sensitivity, specificity, and accuracy.…”
Section: Bacteria Identification and Discriminationmentioning
confidence: 99%
“…With sufficient sensitivity to chemical changes, this specificity is ample to identify subtle phenotype changes. Indeed, individual Raman spectra, with acquisition averaged over entire cells, have been used to distinguish differentiated and pluripotent cells, to identify activated immune cells, and to discriminate between bacterial subtypes. Even at a spectral resolution of 30 cm –1 , rapid bacterial phenotype sorting is possible …”
Section: Introductionmentioning
confidence: 99%